2003
DOI: 10.1103/physrevd.67.103003
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical directional and modulated rates for direct supersymmetric dark matter detection

Abstract: Exotic dark matter together with the vacuum energy (cosmological constant) seem to dominate in the flat Universe. Thus direct dark matter detection is central to particle physics and cosmology. Supersymmetry provides a natural dark matter candidate, the lightest supersymmetric particle (LSP). It is possible to obtain detectable rates, but realystically they are expected to be much lower than the present experimental goals. So one should exploit two characteristic signatures of the reaction, namely the modulati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
64
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 80 publications
0
64
0
Order By: Relevance
“…To proceed further we must evaluate the integral in (28). Firstly, we must select a suitable coordinate system, for example, one with the -axis along the initial WIMP velocity, the -axis in the direction of the outgoing WIMP, and -axis perpendicular to the plane of the other two.…”
Section: The Effect Of the Bound Electron Wave Functionmentioning
confidence: 99%
“…To proceed further we must evaluate the integral in (28). Firstly, we must select a suitable coordinate system, for example, one with the -axis along the initial WIMP velocity, the -axis in the direction of the outgoing WIMP, and -axis perpendicular to the plane of the other two.…”
Section: The Effect Of the Bound Electron Wave Functionmentioning
confidence: 99%
“…In our previous work [56][57][58] we have found that the observed directional rate is characterized by a strong dependence on the angle between the direction of nuclear recoil and the direction of the sun's motion with respect to the center of the galaxy. The apparatus will, of course, be oriented in a direction defined in the local frame, i.e.…”
Section: Introductionmentioning
confidence: 92%
“…So our results apply to all WIMPs. In light of this possibility we will like to explore, which characteristics, if any, of the previous results [56][57][58] persist as a diurnal variation and perhaps predict new signatures. We will see that, to fully exploit the advantages offered by the directional experiments, the detectors should be able to distinguish the head from the tail of the track, i.e.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Additional theoretical tools are the structure of the nucleus, see e.g. [27][28][29][30], and the nuclear matrix elements [31][32][33][34][35]. This paper will focus on the spin dependent WIMP nucleus interaction.…”
Section: Introductionmentioning
confidence: 99%